2016
DOI: 10.1091/mbc.e15-11-0798
|View full text |Cite
|
Sign up to set email alerts
|

RBM4 promotes neuronal differentiation and neurite outgrowth by modulating Numb isoform expression

Abstract: RBM4 modulates alternative exon selection of Numb and up-regulates proneural Mash1 gene expression, possibly via specific Numb isoforms. RBM4 overexpression promotes neuronal cell differentiation. Moreover, RBM4 is essential for neurite outgrowth in primary cortical neurons by modulating specific Numb isoform expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…PKM1 is expressed in energy-consuming tissues, including brain and skeletal muscle, whereas PKM2 is expressed more dominantly in embryonic cells (19). We previously observed a change in expression of Pkm isoforms, i.e., from Pkm2 to Pkm1, during neuronal differentiation of mouse embryonal carcinoma P19 cells (1). We thus further explored the significance and mechanism of this isoform switch during development.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…PKM1 is expressed in energy-consuming tissues, including brain and skeletal muscle, whereas PKM2 is expressed more dominantly in embryonic cells (19). We previously observed a change in expression of Pkm isoforms, i.e., from Pkm2 to Pkm1, during neuronal differentiation of mouse embryonal carcinoma P19 cells (1). We thus further explored the significance and mechanism of this isoform switch during development.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies demonstrated the role of RBM4 in differentiation of muscle and pancreas cells and adipocytes (3)(4)(5). We recently reported that RBM4 is also involved in neuronal differentiation of mouse embryonal carcinoma P19 cells and neural progenitor-derived cells (1). RBM4 promotes the expression of Numb splice isoforms that function during neuronal differentiation as well as neurite outgrowth.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…GREs have been associated to the stabilization of mRNAs 61 and also have been reported as targets of RNA-binding proteins (RBPs) such as CELFs 62 . Among the set of 160 genes with differential inclusion of GRE elements in our neural system, tappAS identified splicing regulators such as Rbm4 (Supplementary Figure 1A), involved in neurogenesis of the mouse embryonic brain 63 , and Tcf12 (Supplementary Figure 1B), known to play an important role in the control of proliferating neural stem cells and progenitor cells during neurogenesis 64 .…”
Section: 'Utr and Cds-varyingmentioning
confidence: 99%
“…RBM4 level is reduced in patients affected with fetal Down syndrome (14). We previously reported that RBM4 modulates alternative splicing of the Notch signaling inhibitor Numb and that RBM4-induced Numb isoforms potentiate the expression of the proneurogenesis gene Mash1 and hence promotes differentiation of mouse neuronal progenitor cells (15). In addition, RBM4 modulates the splice isoform switch of pyruvate kinase M (PKM) and thereby elevates mitochondrial oxidative phosphorylation and facilitates neuronal differentiation of mesenchymal stem cells (10).…”
mentioning
confidence: 99%